Interaction with Slovenia and Slovenian culture and science - Brožek, Josef Marija (Traditiones (Ljubljana), 1999)
The author, psychologist by profession and of Czech origin, reminisces about his encounters with Slovene folk songfs and with colleagues from Slovenia, among them also the employees of the Institute of Ethnomusicology
Keywords: folk music; ljudska glasba; music; glasba